54th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2013
DOI: 10.2514/6.2013-1503
|View full text |Cite
|
Sign up to set email alerts
|

Wing Design as a Symphony of Geographically Dispersed, Multi-disciplinary Undergraduate Students

Abstract: Globalization, technology, and risk sharing business partnerships have changed the landscape of large scale systems integration. In today's business environment, the traditional style of knowledge transfer presuppositions and foundations are inadequate for dissemination of process knowledge in a global multi-cultural environment. The following paper describes a research university -industry approach as well as knowledge transfer strategies for successfully implementing a "Multi-site, cloud based capstone desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Test articles included a scaled fuselage, two newly-designed wings, and interchangeable wing tips (raked tip and a winglet tip). The scaled aircraft was fully 3D printed and is still used for aerodynamics experiments to this day 22 .…”
Section: Projects Summarymentioning
confidence: 99%
“…Test articles included a scaled fuselage, two newly-designed wings, and interchangeable wing tips (raked tip and a winglet tip). The scaled aircraft was fully 3D printed and is still used for aerodynamics experiments to this day 22 .…”
Section: Projects Summarymentioning
confidence: 99%
“…The project demonstrated that students from three institutions in three time zones could effectively collaborate on the design of an aircraft wing assembly. The 2012 -2013 project successfully implemented a "multi-site, cloud-based capstone design project" within a cross-cultural, peer-topeer design-build-test environment [11]. Within this environment students were exposed to the industrial principles of collaborative digital design and manufacturing, targeting complex cybermechanical systems.…”
mentioning
confidence: 99%
“…The structure for such a collaboration relies on mutual agreement and understanding of purposes and objectives. 24 Student outcomes have been documented and proven to be successful 19,25,23, but must now be linked back to the realities of academic degrees, mainly the accreditation process.…”
mentioning
confidence: 99%